2016
DOI: 10.3329/bjar.v41i4.30704
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of some new genearation insecticides and a botanical against mustard aphid and their toxicity to coccinellid predators and foraging honeybees

Abstract: Field studies were carried out to evaluate the efficacy of four new generation insecticides along with a botanical against mustard aphid (Lipaphis erysimi Kalt.) and their toxicity to coccinellid beetles and foraging honeybees during 2014-15 at Bangladesh Agricultural Research Institute (BARI), Gazipur, Bangladesh. Buprofezin 40 SC was found to be the most effective against aphid offering the lowest aphid population (1.56/ top10cm central twig) at 7 days after spraying (DAS) which was statistically identical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Lastly, the obtained results matched those reported by Dutta et al (2016) on their field study to evaluate four insecticides against mustard aphid and their toxicity to coccinellid beetles. They found that among the treatments, azadirachtin 1EC appeared to be safest to coccinellid beetles, while indoxacarb 145 SC was found to be toxic.…”
Section: Aphid Treatmentssupporting
confidence: 81%
“…Lastly, the obtained results matched those reported by Dutta et al (2016) on their field study to evaluate four insecticides against mustard aphid and their toxicity to coccinellid beetles. They found that among the treatments, azadirachtin 1EC appeared to be safest to coccinellid beetles, while indoxacarb 145 SC was found to be toxic.…”
Section: Aphid Treatmentssupporting
confidence: 81%
“…The pooled data on the incidence reveal that dimethoate 30%EC is significantly more effective against L. erysimi (93.09 and 92.94% reduction after three days in first and second treatment, respectively) followed by pyriproxyfen 10%EC and buprofezin 25%SC. Gaikwad et al (2014), Choudhary and Singh (2015), Dutta et al (2016) and Sharma et al (2017) also observed that dimethoate 30%EC is more effective. With pyriproxyfen 10%EC, buprofezin 25%SC, emamectin benzoate 5%SG and pymetrozine 50%WG reduction in incidence ranged from 90.70-79.10% with first, and 90.37-78.51% with second spray, respectively, after three days of spray.…”
Section: Resultsmentioning
confidence: 85%
“…The findings of this study revealed that, imidacloprid, botanical mix, and neem seed extract were proved relatively safer to the lady bird beetles. Similarly, Dutta et al (2016) reported that azadiractin 1% EC was less toxic product to coccinellid beetles and foraging honey bees. On the contrary, Ali and Zedan (2015) studied the nontarget effect of five insecticides (viz.…”
Section: Discussionmentioning
confidence: 92%